Antistatic aluminum-plastic film, preparation method and application in lithium battery packaging
Patent Information
- Application Number
- CN202611018303.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-08-28
AI Technical Summary
[0032] This invention prepares a dialdehyde-based alkenyl functionalized modifier, which is then used as a linker. Through a Schiff base reaction with amino-functionalized carbon black and amino-functionalized reduced graphene oxide, chemical bonding between carbon black and graphene is achieved, resulting in carbon black-graphene hybrid particles. Zero-dimensional carbon black is anchored on the surface of two-dimensional graphene sheets, creating a point-to-surface synergistic effect. The carbon black particles act as conductive bridges between graphene sheets, forming a continuous conductive network. This allows electrons to transition between graphene sheets and carbon black particles, solving the problem that a high filling amount is required to form a conductive path when carbon black is used alone. This increases the number of conductive channels, reduces contact resistance, and endows the material with excellent antistatic properties.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of packaging materials technology, and in particular to an antistatic aluminum-plastic film, its preparation method, and its application in lithium battery packaging. Background Technology
[0002] With the rapid development of the electric vehicle industry, the demand for power batteries has increased dramatically. Lithium iron phosphate (LFP) batteries have become the preferred choice for power batteries due to their excellent cycle life, safety, and low cost. As the cathode material in lithium-ion batteries, the demand for LFP is also rising significantly. When used in lithium-ion batteries, LFP powder is a submicron to micron-sized powder with a huge specific surface area (10-30 m²). 2 / g), with high surface activity, is extremely sensitive to moisture and easily absorbs moisture, making high-barrier aluminum-plastic film an inevitable choice for packaging or storage;
[0003] During packaging, transportation, storage, and disposal, submicron to micron-sized lithium iron phosphate powder is highly susceptible to static electricity accumulation due to friction between particles and between particles and the inner layer of the packaging. This not only makes it difficult to discharge the powder from the inner wall of the packaging, causing agglomeration and waste, but may also lead to dust explosions due to electrostatic discharge sparks. Therefore, it is necessary to modify the polyethylene inner layer of the aluminum-plastic film with antistatic properties to form a static dissipation network in the inner layer, so that static charge can be discharged in time and not accumulated. Combined with the excellent barrier properties of the aluminum-plastic film, a barrier-antistatic protection system is formed to prevent external environmental contamination of lithium iron phosphate powder, avoid static electricity hazards, and ensure the quality stability and production safety of lithium battery raw materials.
[0004] Conductive fillers can be used to achieve antistatic modification of polyethylene materials. Carbon black is widely used in the field of antistatic modification due to its low cost and stable performance. However, as a zero-dimensional particulate filler, carbon black requires point-to-point contact between particles to form a continuous conductive path when used alone. Therefore, the filling amount is relatively high, generally 5-15 wt%, to achieve the antistatic effect, which will negatively affect the heat-sealing performance of polyethylene. Graphene, on the other hand, is a two-dimensional sheet material that can form a continuous conductive path through surface-to-surface contact. When the two are compounded, carbon black particles effectively fill the network between graphene sheets, forming a denser point-to-surface three-dimensional conductive network, which helps charge transport, greatly increases the number of conductive channels, and enriches the electron transport paths. This allows antistatic requirements to be met with a lower filler content without affecting heat-sealing performance. Summary of the Invention
[0005] This invention addresses the dual requirements of high barrier properties and antistatic properties in lithium iron phosphate cathode material packaging for lithium batteries. It prepares carbon black-graphene hybrid particles, achieving chemical bonding between carbon black and graphene through a Schiff base reaction between a dialdehyde-based alkenyl functionalized modifier and amino-functionalized reduced graphene oxide, thus constructing a point-to-surface synergistic conductive network. These hybrid particles undergo a free radical addition grafting reaction with linear low-density polyethylene resin to obtain a carbon black-graphene polyethylene composite masterbatch. This masterbatch is then blended with metallocene linear low-density polyethylene resin and blow-molded into a film as the inner layer. This film is then dry-laminated with nylon / aluminum foil to produce an aluminum-plastic film, maintaining heat-sealing performance while imparting excellent antistatic properties.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] An antistatic aluminum-plastic film is made by dry lamination of an outer nylon film, a middle aluminum foil layer and an inner polyethylene composite film.
[0008] The polyethylene composite film is composed of 60-80wt% metallocene linear low-density polyethylene resin and 20-40wt% carbon black-graphene polyethylene composite masterbatch.
[0009] Carbon black-graphene polyethylene composite masterbatch comprises the following raw materials in parts by weight:
[0010] 9-9.6 parts linear low-density polyethylene resin;
[0011] 0.3-0.6 parts carbon black-graphene hybrid particles;
[0012] 0.03-0.06 parts initiator;
[0013] The carbon black-graphene hybrid particles are prepared by a Schiff base reaction of a dialdehyde alkenyl functionalized modifier with amino-functionalized carbon black and amino-functionalized reduced graphene oxide. The mass ratio of amino-functionalized carbon black, amino-functionalized reduced graphene oxide and dialdehyde alkenyl functionalized modifier is 1:0.2-0.4:1-3.
[0014] Preferably, the preparation method of the dialdehyde alkenyl functionalized modifier is as follows:
[0015] Diethanolamine undergoes an amine addition reaction with allyl methacrylate via a secondary amine and an α-β-unsaturated alkenyl group, with the molar ratio of diethanolamine to allyl methacrylate controlled at 1:1; a dihydroxyalkenyl-functionalized intermediate is obtained.
[0016] The dihydroxyenyl functionalized intermediate undergoes an esterification reaction of hydroxyl groups and acyl chloride with chloroacetyl chloride, with the molar ratio of the dihydroxyenyl functionalized intermediate to chloroacetyl chloride controlled at 1:2; thus, the dichloroenyl functionalized intermediate is obtained.
[0017] The dichloroalkenyl functionalized intermediate undergoes a substitution reaction between the chlorine functional group and the hydroxyl group of p-hydroxybenzaldehyde. By controlling the molar ratio of the dichloroalkenyl functionalized intermediate to p-hydroxybenzaldehyde to be 1:2, a dialdehyde-alkenyl functionalized modifier is prepared.
[0018] Preferably, the amino-functionalized carbon black is prepared by silanizing carbon black with hydroxyl-rich surface by 3-aminopropyltriethoxysilane; the mass ratio of 3-aminopropyltriethoxysilane to carbon black is 0.04-0.1:1.
[0019] Preferably, the amino-functionalized reduced graphene oxide is prepared by silanizing graphene oxide with 3-aminopropyltriethoxysilane and then reducing it with diethanolamine as a reducing agent; the mass ratio of 3-aminopropyltriethoxysilane, diethanolamine and graphene oxide is 5-10:4-6:1.
[0020] Preferably, the average particle size of the carbon black is 5-15 nm.
[0021] Preferably, the average sheet diameter of the graphene oxide is 2-8 μm.
[0022] Preferably, the initiator is dicumyl peroxide or benzoyl peroxide.
[0023] A method for preparing an antistatic aluminum-plastic film includes the following steps:
[0024] Step 1: Initiator, carbon black-graphene hybrid particles and linear low-density polyethylene resin are added to a twin-screw extruder according to the formula. After melt grafting reaction, the mixture is extruded and granulated to obtain carbon black-graphene polyethylene composite masterbatch.
[0025] The twin-screw extruder has the following temperature zones: Zone 1: 150-170℃; Zone 2: 170-190℃; Zone 3: 190-210℃; Zone 4: 200-225℃; Zone 5: 200-220℃; Zone 6: 190-215℃; Screw speed: 60-120 r / min; Melt grafting reaction time: 5-20 min.
[0026] Step 2: Using metallocene linear low-density polyethylene resin and carbon black-graphene polyethylene composite masterbatch as raw materials, the raw materials are put into the hopper of a single screw extrusion blown film machine according to the formula dosage, stirred and mixed evenly, the molten resin is gathered at the die head through the distributor, extruded and blown through the die head, cooled, and wound up to obtain a polyethylene composite film.
[0027] The temperatures of each zone of the single-screw extrusion blown film machine are as follows: Zone 1 125-135℃, Zone 2 150-160℃, Zone 3 170-180℃, flow channel temperature 165-175℃, screw speed 30-50 r / min, and blow-up ratio 2.3-2.6.
[0028] Step 3: Apply two-component polyurethane adhesive between the outer nylon film and the middle aluminum foil layer, and between the middle aluminum foil layer and the inner polyethylene composite film, respectively. After drying, laminating, and curing, an antistatic aluminum-plastic film is obtained; wherein the dry adhesive coating amount is 2.0-5.0 g / m². 2 The drying temperature is 60-90℃, the composite pressure is 0.2-0.8MPa, the curing temperature is 40-60℃, and the curing time is 24-72h. The side of the polyethylene composite film that is laminated with the aluminum foil is corona treated, and the surface tension after corona treatment is 38-44mN / m. The other side of the polyethylene composite film serves as the inner heat-sealing layer of the antistatic aluminum-plastic film.
[0029] Preferably, the outer nylon film has a thickness of 15-25 μm, the middle aluminum foil layer has a thickness of 7-20 μm, and the inner polyethylene composite film has a thickness of 95-110 μm.
[0030] An application of an antistatic aluminum-plastic film, wherein the antistatic aluminum-plastic film is used for packaging lithium iron phosphate powder, a cathode material for lithium batteries.
[0031] The beneficial effects of this invention are as follows:
[0032] This invention prepares a dialdehyde-based alkenyl functionalized modifier, which is then used as a linker. Through a Schiff base reaction with amino-functionalized carbon black and amino-functionalized reduced graphene oxide, chemical bonding between carbon black and graphene is achieved, resulting in carbon black-graphene hybrid particles. Zero-dimensional carbon black is anchored on the surface of two-dimensional graphene sheets, creating a point-to-surface synergistic effect. The carbon black particles act as conductive bridges between graphene sheets, forming a continuous conductive network. This allows electrons to transition between graphene sheets and carbon black particles, solving the problem that a high filling amount is required to form a conductive path when carbon black is used alone. This increases the number of conductive channels, reduces contact resistance, and endows the material with excellent antistatic properties.
[0033] Carbon black-graphene hybrid particles are antistatic functional components. Their surfaces contain alkenyl functional groups. Through the action of an initiator, they undergo a free radical addition grafting reaction with linear low-density polyethylene resin to obtain carbon black-graphene polyethylene composite masterbatch. This improves the dispersibility and interfacial bonding of the hybrid particles, ensuring the stability of antistatic performance. Using carbon black-graphene polyethylene composite masterbatch and metallocene linear low-density polyethylene resin as raw materials, a polyethylene composite film is prepared. With nylon film as the outer layer, aluminum foil as the middle layer, and polyethylene composite film as the inner layer, an antistatic aluminum-plastic film is prepared by dry lamination.
[0034] The experimental results show that the aluminum-plastic film prepared by this invention has good barrier properties (oxygen permeability ≤ 0.5 cm). 3 / (m 2•24h•0.1MPa), water vapor transmission rate ≤0.5g / (m 2 Excellent heat-sealing performance (heat-sealing strength > 50 N / 15 mm) and antistatic properties (surface resistivity of polyethylene composite film is 2.68 × 10⁻⁶). 6 -8.42×10 8 Within the Ω range, the surface resistivity of the inner layer of the composite antistatic aluminum-plastic film is 3.05 × 10⁻⁶. 6 -9.10×10 8 Ω), while ensuring barrier and heat-sealing performance, can also avoid waste and dust explosion risks caused by static electricity accumulation, making it suitable for packaging lithium iron phosphate powder, the positive electrode material of lithium batteries. Detailed Implementation
[0035] Example 1:
[0036] The preparation principle of dialdehyde alkenyl functionalized modifiers is as follows:
[0037] Diethanolamine undergoes an amine addition reaction with allyl methacrylate via a secondary amine and an α-β-unsaturated alkenyl group, with the molar ratio of diethanolamine to allyl methacrylate controlled at 1:1; a dihydroxyalkenyl-functionalized intermediate is obtained.
[0038] The dihydroxyenyl functionalized intermediate undergoes an esterification reaction of hydroxyl groups and acyl chloride with chloroacetyl chloride, with the molar ratio of the dihydroxyenyl functionalized intermediate to chloroacetyl chloride controlled at 1:2; thus, the dichloroenyl functionalized intermediate is obtained.
[0039] A dichloroalkenyl functionalized intermediate undergoes a substitution reaction between the chlorine functional group and the hydroxyl group of p-hydroxybenzaldehyde. By controlling the molar ratio of the dichloroalkenyl functionalized intermediate to p-hydroxybenzaldehyde to be 1:2, a dialdehyde-alkenyl functionalized modifier is prepared, the chemical structure of which is as follows:
[0040] ;
[0041] The preparation method of the dialdehyde alkenyl functionalized modifier includes the following steps:
[0042] (1) Preparation of dihydroxyenyl functionalized intermediates:
[0043] 1 g of diethanolamine, 1.3 mL of allyl methacrylate and 10 mL of anhydrous methanol were added to a three-necked flask, and nitrogen gas was introduced for protection. The mixture was stirred at 200 r / min for 30 min at room temperature. The temperature was then raised to 45 °C and stirred at a constant temperature for 5 h. Methanol was removed by rotary evaporation and the mixture was dried in a vacuum drying oven at 50 °C for 10 h to obtain the dihydroxyalkenyl functionalized intermediate.
[0044] (2) Preparation of dichloroenyl functionalized intermediates:
[0045] 2.3 g of the dihydroxyenyl functionalized intermediate and 20 mL of dichloromethane were added to a three-necked flask, and then stirred at 200 r / min for 10 min in an ice-water bath. After adding 1.6 mL of chloroacetyl chloride for 0.5 h, the ice-water bath was removed, the temperature was raised to room temperature, and the reaction was allowed to proceed for 2 h. The reaction solution was then poured into ice water, and solid sodium carbonate powder was added until no more bubbles escaped. The organic layer was washed three times with deionized water, and the organic layer was separated. The aqueous phase was extracted with ethyl acetate, the organic phases were combined, dried with anhydrous calcium chloride, filtered, rotary evaporated, and dried in a vacuum drying oven at 50 °C for 10 h to obtain the dichloroenyl functionalized intermediate.
[0046] (3) Preparation of dialdehyde alkenyl functionalized modifiers:
[0047] 3.8 g of dichloroalkenyl functionalized intermediate, 2.42 g of p-hydroxybenzaldehyde, 2 g of anhydrous potassium carbonate and 20 mL of N,N-dimethylformamide were added to a three-necked flask. The mixture was stirred at 200 r / min for 30 min, and then the temperature was raised to 90 °C and the reaction was allowed to proceed for 5 h. The reaction solution was poured into ice water, and a solid precipitated. The pH was adjusted to neutral with dilute hydrochloric acid, filtered, and dried in a vacuum drying oven at 50 °C for 10 h to obtain the dialdehyde alkenyl functionalized modifier.
[0048] The 1H NMR characterization results of the dialdehyde alkenyl functionalized modifier are as follows:
[0049] 1 H NMR (400MHz, DMSO-D6, δ, ppm): 1.11-1.13 (d, 3H), 2.40-2.47 (m, 1H), 2.59-2.71 (m, 2H), 2.79-2.88 (m, 4H), 4.23-4.30 (m, 4H) ), 4.58-4.63(m, 2H), 4.67(s, 4H), 5.27-5.34(m, 2H), 5.87-5.94(m, 1H), 7.01-7.03(d, 4H), 7.86-7.88(d, 4H), 9.89(s, 2H).
[0050] Example 2:
[0051] The preparation principle of amino-functionalized carbon black is as follows: carbon black is modified by silanization with 3-aminopropyltriethoxysilane to obtain amino-functionalized carbon black; the mass ratio of 3-aminopropyltriethoxysilane to carbon black is controlled to be 0.04-0.1:1.
[0052] The specific preparation method of amino-functionalized carbon black is as follows:
[0053] 0.2 g of 3-aminopropyltriethoxysilane, 3 mL of acetic acid, and 30 mL of anhydrous ethanol were added to a beaker and stirred at 500 r / min for 1 h to form a 3-aminopropyltriethoxysilane solution. 3 g of carbon black (average particle size 12 nm) and 90 mL of anhydrous ethanol were added to the beaker and stirred for 15 min to form a carbon black dispersion. The carbon black dispersion was slowly added to the 3-aminopropyltriethoxysilane solution and stirred for 1 h. The temperature was then raised to 80 °C and stirred continuously for 4 h. After centrifugation, the mixture was washed with anhydrous ethanol and deionized water until neutral and dried in a vacuum drying oven at 80 °C for 10 h to obtain amino-functionalized carbon black.
[0054] FT-IR (KBr, ν / cm) -1 ): 3400, 3300, 2927, 2857, 1578, 1098;
[0055] 3400cm -1 The characteristic peak of -NH2 appears at 3300 cm⁻¹. -1 The characteristic peak of -OH appears at 2927 cm⁻¹. -1 2857cm -1 The characteristic peak of CH appears at 1578 cm⁻¹. -1 A characteristic peak of -NH2 appears at 1098 cm⁻¹. -1 The presence of the characteristic peak -Si-OC at this location indicates that 3-aminopropyltriethoxysilane has been modified onto the carbon black surface;
[0056] The preparation principle of amino-functionalized reduced graphene oxide is as follows: 3-aminopropyltriethoxysilane is used to silanize graphene oxide, and then diethanolamine is used as a reducing agent to reduce it to obtain amino-functionalized reduced graphene oxide; the mass ratio of 3-aminopropyltriethoxysilane, diethanolamine and graphene oxide is controlled to be 5-10:4-6:1.
[0057] The specific preparation method of amino-functionalized reduced graphene oxide is as follows:
[0058] 0.5 g of graphene oxide (average sheet diameter of 5 μm) and 750 mL of ethanol aqueous solution with a volume ratio of 2:1 were added to a four-necked flask and stirred at 600 r / min for 1 h. Then, 5 g of 3-aminopropyltriethoxysilane was added and stirred at room temperature for 12 h. The mixture was filtered, washed three times each with anhydrous ethanol and deionized water, and dried in a vacuum drying oven at 80 °C for 10 h to obtain amino-functionalized graphene oxide.
[0059] 0.5g of amino-functionalized graphene oxide and 500mL of deionized water were added to a beaker and stirred for 40min. Then, 2g of diethanolamine was slowly added and stirred at room temperature for 12h. The mixture was washed with anhydrous ethanol and deionized water until neutral and then dried in a vacuum drying oven at 80℃ for 10h to obtain amino-functionalized reduced graphene oxide.
[0060] FT-IR (KBr, ν / cm) -1 ):
[0061] Amino-functionalized graphene oxide: 3408, 3380, 2933, 2851, 1731, 1562, 1223, 1105, 1052.
[0062] 3408cm -1 A characteristic peak of -NH2 appears at 3380 cm⁻¹. -1 The characteristic peak of -OH appears at 2933 cm⁻¹. -1 2851cm -1 The characteristic peak of -CH2 appears at 1731 cm⁻¹. -1 The characteristic peak of C=O appears at 1562 cm⁻¹. -1 A characteristic peak of -NH2 appears at 1223 cm⁻¹. -1 The characteristic peak of -COO- appears at 1105 cm⁻¹. -1 The characteristic peak of Si-OC appears at 1052 cm⁻¹. -1 The presence of a characteristic peak for COC indicates that 3-aminopropyltriethoxysilane has been modified onto the surface of graphene oxide.
[0063] Amino-functionalized reduced graphene oxide: 3405, 3376, 2936, 2854, 1566, 1103.
[0064] 3405cm -1 A characteristic peak of -NH2 appears at 3376 cm⁻¹. -1 The characteristic peak of -OH appears at 2933 cm⁻¹. -1 2851cm -1 The characteristic peak of -CH2 appears at 1731 cm⁻¹. -1 The characteristic peak at C=O disappears at 1566 cm⁻¹. -1 A characteristic peak of -NH2 appears at 1223 cm⁻¹. -1 The characteristic peak of -COO- disappears at 1103 cm⁻¹. -1 The characteristic peak of Si-OC appears at 1052 cm⁻¹. -1 The disappearance of the characteristic peak of COC indicates that graphene oxide has been reduced to graphene.
[0065] Example 3:
[0066] The preparation principle of carbon black-graphene hybrid particles is as follows:
[0067] Using a dialdehyde alkenyl functionalized modifier as a linker, carbon black and graphene are chemically bonded by reacting with amino-functionalized carbon black and amino-functionalized reduced graphene oxide through a Schiff base reaction, thus obtaining carbon black-graphene hybrid particles. The mass ratio of amino-functionalized carbon black, amino-functionalized reduced graphene oxide and dialdehyde alkenyl functionalized modifier is controlled to be 1:0.2-0.4:1-3.
[0068] The specific preparation method of carbon black-graphene hybrid particles is as follows:
[0069] 1 g of amino-functionalized carbon black and 200 mL of dimethyl sulfoxide were added to a beaker and stirred at 600 r / min for 30 min. Then, 0.3 g of amino-functionalized reduced graphene oxide was added and stirred for another 30 min. Next, 2.5 g of dialdehyde alkenyl functionalizing modifier was added. The temperature was heated to 65 °C and stirred for 5 h. After cooling to room temperature, the mixture was centrifuged and washed three times with dimethyl sulfoxide and anhydrous ethanol, respectively. Finally, the mixture was dried in a vacuum drying oven at 80 °C for 10 h to obtain carbon black-graphene hybrid particles.
[0070] FT-IR (KBr, ν / cm) -1 ): 3397, 3061, 3027, 2937, 2861, 1732, 1665, 1600, 1589, 1573, 1501, 1452, 1250, 1109;
[0071] 3397cm -1 The characteristic peak of -OH / NH appears at 3061 cm⁻¹. -1 The characteristic peak of CH in a carbon-carbon double bond appears at 3027 cm⁻¹. -1 Characteristic peaks of CH in the benzene ring appear at 2937 and 2861 cm⁻¹. -1 A characteristic peak of -CH2 appears at 1732 cm⁻¹. -1 The characteristic peak of the ester group C=O appears at 1665 cm⁻¹. -1 A characteristic peak of the C=C bond appears at 1573 cm⁻¹. -1 The characteristic peak of the C=N Schiff base bond appears at 1600 cm⁻¹. -1 1589cm -1 1501cm -1 1452cm -1 The characteristic peak of the benzene ring skeleton appears at 1250 cm⁻¹. -1 The characteristic peak of CO appears at 1109 cm⁻¹. -1 The characteristic peaks of Si-OC appear at this location;
[0072] Example 4:
[0073] The preparation principle of carbon black-graphene polyethylene composite masterbatch is as follows:
[0074] Under molten conditions, dicumyl peroxide initiator causes linear low-density polyethylene resin to generate free radicals, which then undergo free radical addition grafting reaction with the alkenyl functional groups on the surface of carbon black-graphene hybrid particles, thereby combining carbon black-graphene hybrid particles with linear low-density polyethylene in the form of covalent bonds to obtain carbon black-graphene polyethylene composite masterbatch.
[0075] Carbon black-graphene polyethylene composite masterbatch comprises the following raw materials in parts by weight:
[0076] 9.4 parts linear low-density polyethylene resin (model 7042);
[0077] 0.55 parts carbon black-graphene hybrid particles;
[0078] 0.05 parts dicumyl peroxide;
[0079] The preparation method of carbon black-graphene polyethylene composite masterbatch is as follows:
[0080] Dicumyl peroxide, carbon black-graphene hybrid particles, and linear low-density polyethylene resin were added to a twin-screw extruder and melt-blended for 20 min, reacted for 15 min, and then extruded and granulated to obtain carbon black-graphene polyethylene composite masterbatch. The temperatures of zone 1 were 160℃, zone 2 were 180℃, zone 3 was 200℃, zone 4 was 220℃, zone 5 was 210℃, and zone 6 was 210℃. The screw speed was 80 r / min.
[0081] Characterization of carbon black-graphene polyethylene composite masterbatch:
[0082] The carbon black-graphene-polyethylene composite masterbatch was purified by Soxhlet extraction. 5g of carbon black-graphene-polyethylene composite masterbatch was wrapped in quantitative filter paper, placed in a Soxhlet extractor, and heated with xylene to continuous reflux for 24h. After that, fresh xylene was replaced and extraction was continued for 6h. The extracted solid was taken out, washed three times with acetone to remove residual xylene, and dried in an 80℃ vacuum drying oven to constant weight to obtain purified carbon black-graphene-polyethylene composite masterbatch.
[0083] FT-IR (KBr, ν / cm) -1 ): 3389, 3024, 2931, 2859, 1735, 1603, 1585, 1577, 1504, 1469, 1456, 1253, 1111, 724;
[0084] 3389cm -1 The characteristic peak of -OH / NH appears at 3061 cm⁻¹.-1 The characteristic peak of CH in the carbon-carbon double bond disappears at 3024 cm⁻¹. -1 Characteristic peaks of CH in the benzene ring appear at 2931 and 2859 cm⁻¹. -1 The characteristic peak of -CH2 appears at 1735 cm⁻¹. -1 The characteristic peak of the ester group C=O appears at 1665 cm⁻¹. -1 The characteristic peak of the C=C bond disappears at 1577 cm⁻¹. -1 The characteristic peak of the C=N Schiff base bond appears at 1603 cm⁻¹. -1 1585cm -1 1504cm -1 1456cm -1 The characteristic peak of the benzene ring skeleton appears at 1469 cm⁻¹. -1 724cm -1 A characteristic peak of long-chain -CH2 appears at 1253 cm⁻¹. -1 The characteristic peak of CO appears at 1111 cm⁻¹. -1 The characteristic peak of Si-OC appears at this location.
[0085] Carbon black polyethylene composite masterbatch a comprises the following raw materials in parts by weight:
[0086] 9.45 parts linear low-density polyethylene resin (model 7042);
[0087] 0.55 parts carbon black;
[0088] The preparation method of carbon black polyethylene composite masterbatch a is as follows:
[0089] Carbon black and linear low-density polyethylene resin were added to a twin-screw extruder and melt-blended for 40 min. The mixture was then extruded and granulated to obtain carbon black-polyethylene composite masterbatch a. The temperatures of zone 1, zone 2, zone 3, zone 4, zone 5, and zone 6 were 150℃, 180℃, 175℃, 170℃, and 165℃, and the screw speed was 80 r / min.
[0090] Carbon black polyethylene composite masterbatch b comprises the following raw materials in parts by weight:
[0091] 8.5 parts linear low-density polyethylene resin (model 7042);
[0092] 1.5 parts carbon black;
[0093] The preparation method of carbon black polyethylene composite masterbatch b is the same as that of carbon black polyethylene composite masterbatch a.
[0094] Example 5:
[0095] Antistatic aluminum-plastic film a is made by dry lamination of an outer nylon film, a middle aluminum foil layer and an inner polyethylene composite film a.
[0096] The outer nylon film has a thickness of 15μm, the middle aluminum foil layer has a thickness of 12μm, and the inner polyethylene composite film a has a thickness of 100μm.
[0097] The dry lamination process is as follows: First, apply a two-component polyurethane adhesive to one side of the aluminum foil, controlling the dry adhesive application rate to be 3.0 g / m². 2 After drying in three drying tunnels at 60℃, 70℃, and 80℃, the film is laminated with a nylon film at a lamination temperature of 60℃ and a lamination pressure of 0.5MPa to obtain a nylon / aluminum foil composite film. Then, a two-component polyurethane adhesive is coated on the other side of the aluminum foil, with the dry adhesive coating amount controlled at 3.0 g / m². 2 After drying in three drying tunnels at 60℃, 70℃ and 80℃, it is laminated with a corona-treated polyethylene composite film a (surface tension of 42mN / m) at a lamination temperature of 60℃ and a lamination pressure of 0.5MPa. After lamination, it is cured at 50℃ for 48 hours to obtain an antistatic aluminum-plastic film a.
[0098] The corona-treated surface of the polyethylene composite film a is laminated with aluminum foil, while the untreated surface serves as the inner heat-sealing layer of the antistatic aluminum-plastic film.
[0099] Polyethylene composite film a, comprising the following raw materials in parts by weight:
[0100] 24 parts of metallocene linear low-density polyethylene resin (model SP1520);
[0101] 6 parts carbon black-graphene polyethylene composite masterbatch;
[0102] The preparation method of polyethylene composite film a is as follows:
[0103] The raw materials are put into the hopper of a single-screw extrusion blown film machine according to the formula dosage, stirred and mixed evenly, the molten resin is gathered at the die head through the distributor, extruded and blown through the die head, cooled, and wound up to obtain a polyethylene composite film a with a thickness of 100μm.
[0104] The temperatures of each zone of the single-screw extrusion blown film machine are as follows: Zone 1: 130℃, Zone 2: 155℃, Zone 3: 175℃, flow channel temperature: 170℃, screw speed: 40r / min, and blow-up ratio: 2.5.
[0105] Example 6:
[0106] Antistatic aluminum-plastic film b is made by dry lamination of an outer nylon film, a middle aluminum foil layer, and an inner polyethylene composite film b; the preparation method of antistatic aluminum-plastic film b is the same as that of antistatic aluminum-plastic film a.
[0107] Polyethylene composite film b comprises the following raw materials in parts by weight:
[0108] 21 parts of metallocene linear low-density polyethylene resin (model SP1520);
[0109] 9 parts carbon black-graphene polyethylene composite masterbatch;
[0110] The preparation method of polyethylene composite film b is the same as that of polyethylene composite film a.
[0111] Example 7:
[0112] Antistatic aluminum-plastic film c is made by dry lamination of an outer nylon film, a middle aluminum foil layer and an inner polyethylene composite film c; the preparation method of antistatic aluminum-plastic film c is the same as that of antistatic aluminum-plastic film a.
[0113] Polyethylene composite film c comprises the following raw materials in parts by weight:
[0114] 18 parts of metallocene linear low-density polyethylene resin (model SP1520);
[0115] 12 parts carbon black-graphene polyethylene composite masterbatch;
[0116] The preparation method of polyethylene composite film c is the same as that of polyethylene composite film a.
[0117] Comparative Example 1:
[0118] Antistatic aluminum-plastic film d is made by dry lamination of an outer nylon film, a middle aluminum foil layer and an inner polyethylene composite film d; the preparation method of antistatic aluminum-plastic film d is the same as that of antistatic aluminum-plastic film a.
[0119] Polyethylene composite film d comprises the following raw materials in parts by weight:
[0120] 18 parts of metallocene linear low-density polyethylene resin (model SP1520);
[0121] 12 parts carbon black polyethylene composite masterbatch a;
[0122] The preparation method of polyethylene composite film d is the same as that of polyethylene composite film a.
[0123] Comparative Example 2:
[0124] Antistatic aluminum-plastic film e is made by dry lamination of an outer nylon film, a middle aluminum foil layer, and an inner polyethylene composite film e; the preparation method of antistatic aluminum-plastic film e is the same as that of antistatic aluminum-plastic film a.
[0125] Polyethylene composite film e comprises the following raw materials in parts by weight:
[0126] 18 parts of metallocene linear low-density polyethylene resin (model SP1520);
[0127] 12 parts carbon black polyethylene composite masterbatch b;
[0128] The preparation method of polyethylene composite film e is the same as that of polyethylene composite film a.
[0129] Performance testing:
[0130] I. Antistatic performance test:
[0131] The surface resistance of polyethylene composite film and the inner polyethylene heat-sealing cover of antistatic aluminum-plastic film were tested according to GB / T 31838.3-2019. Before the test, the samples were cut into 100mm×100mm pieces and conditioned for 24 hours in an environment with a temperature of 23±2℃ and a relative humidity of 50±5%. The test voltage was 100V, and 5 points were tested at different locations for each sample and the average value was taken. When testing the antistatic aluminum-plastic film, the test surface was the side of the polyethylene composite film that was not laminated with the aluminum foil, i.e., the inner heat-sealing cover of the final packaging material.
[0132] II. Electrostatic Attenuation Performance Test:
[0133] The electrostatic decay performance of the inner polyethylene heat-sealing cover of the antistatic aluminum-plastic film was tested using an electrostatic decay tester. Before the test, the sample was conditioned for 24 hours in an environment with a temperature of 23±2℃ and a relative humidity of 50±5%. Initial voltages of +5000V and -5000V were applied respectively, and the time required for the voltage to decay to ±500V was recorded. Each sample was tested 5 times and the average value was taken.
[0134] III. Heat Sealing Performance Test
[0135] The heat-sealing strength of antistatic aluminum-plastic film was tested according to GB / T 22638.7-2016. Two pieces of antistatic aluminum-plastic film with polyethylene inner heat-sealing surfaces were stacked together and heat-sealed using a heat-sealing machine. The heat-sealing temperature was 160℃, the heat-sealing pressure was 0.6MPa, and the heat-sealing time was 6s. After heat-sealing, the film was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 2 hours. Then, the film was cut into samples with a width of 15mm and a clamp spacing of 50mm. A 180° peel test was performed at a speed of 300mm / min. Five samples were tested in each group and the average value was taken.
[0136] IV. Interlayer peel strength test
[0137] The interlayer peel strength of the antistatic aluminum-plastic film was tested according to GB / T 8808-1988. The sample was cut into 15mm wide specimens, and the 180° peel strength between the nylon film / aluminum foil layer and the aluminum foil layer / polyethylene composite film layer was tested respectively. The peeling speed was 300mm / min. Five specimens were tested in each group and the average value was taken.
[0138] V. Barrier Performance Test
[0139] Oxygen barrier performance was tested according to GB / T 1038.1-2022, with a test temperature of 23±2℃ and a pressure difference of 0.1MPa across the sample. Water vapor transmission was tested according to GB / T 1037-2021, with test conditions of 38±0.5℃ and 90±2% relative humidity; when the test result is lower than the detection limit of the instrument or method, it is recorded as ≤0.5.
[0140] VI. Pinhole Test
[0141] The pinhole situation of antistatic aluminum-plastic film was tested using the light transmission method. The sample was placed in a dark box and observed under strong light source to see if any light-transmitting points existed in the aluminum foil layer. The testing area for each sample was no less than 0.1 μm². 2 Record the pinhole situation.
[0142] VII. Performance stability test after kneading
[0143] The antistatic aluminum-plastic film was subjected to a rubbing treatment. After the sample was cut to the specified size, it was fixed on the rubbing test machine. The rubbing angle was 400°, the rubbing horizontal stroke was 80mm, the rubbing frequency was 45 times / min, and the number of rubbing times was 270. After rubbing, the sample was conditioned in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24h. Then the surface resistance, oxygen permeability and water vapor permeability of its inner polyethylene heat-sealing cover were tested.
[0144] The test results are as follows:
[0145] Table 1. Surface resistance and electrostatic attenuation results of the inner layer of polyethylene composite film and aluminum-plastic film.
[0146] serial number Surface resistance of polyethylene composite film (Ω) Surface resistance of the inner layer of antistatic aluminum-plastic film (Ω) +5000V decays to +500V in seconds. -5000V decays to -500V in seconds. Aluminum-plastic film a <![CDATA[8.42×10 8 ]]> <![CDATA[9.10×10 8 ]]> 2.8 3.1 Aluminum-plastic film b <![CDATA[9.86×10 7 ]]> <![CDATA[1.08×10 8 ]]> 0.82 0.90 Aluminum-plastic film c <![CDATA[2.68×10 6 ]]> <![CDATA[3.05×10 6 ]]> 0.12 0.14 Aluminum-plastic film d <![CDATA[4.32×10 12 ]]> <![CDATA[4.85×10 12 ]]> >60 >60 Aluminum-plastic film e <![CDATA[7.53×10 7 ]]> <![CDATA[8.20×10 7 ]]> 0.65 0.72
[0147] Table 2 Results of heat-sealing strength and interlayer peel strength of aluminum-plastic film
[0148] serial number Heat seal strength / N / 15mm Nylon / Aluminum Foil Peel Strength / N / 15mm Aluminum foil / PE peel strength / N / 15mm Aluminum-plastic film a 53.6 4.8 5.2 Aluminum-plastic film b 52.3 4.7 5.1 Aluminum-plastic film c 51.1 4.6 4.9 Aluminum-plastic film d 46.4 4.5 4.6 Aluminum-plastic film e 35.2 4.2 4.1
[0149] Table 3. Barrier performance and pinhole detection results of aluminum-plastic film
[0150] serial number <![CDATA[Oxygen transmission rate / [cm 3 / (m 2 ·24h·0.1MPa)]]]> <![CDATA[Water vapor transmission rate / [g / (m 2 ·24h)]]]> Pinhole situation Aluminum-plastic film a ≤0.5 ≤0.5 Not detected Aluminum-plastic film b ≤0.5 ≤0.5 Not detected Aluminum-plastic film c ≤0.5 ≤0.5 Not detected Aluminum-plastic film d ≤0.5 ≤0.5 Not detected Aluminum-plastic film e ≤0.5 ≤0.5 Not detected
[0151] Table 4 Results after kneading aluminum-plastic film
[0152] serial number Inner layer surface resistance (Ω) after kneading <![CDATA[Oxygen transmission rate / [cm 3 / (m 2 ·24h·0.1MPa)]]]> <![CDATA[Water vapor transmission rate / [g / (m 2 ·24h)]]]> Aluminum-plastic film a <![CDATA[9.84×10 8 ]]> ≤0.5 ≤0.5 Aluminum-plastic film b <![CDATA[1.21×10 8 ]]> ≤0.5 ≤0.5 Aluminum-plastic film c <![CDATA[3.35×10 6 ]]> ≤0.5 ≤0.5 Aluminum-plastic film d <![CDATA[6.82×10 12 ]]> ≤0.5 ≤0.5 Aluminum-plastic film e <![CDATA[1.27×10 8 ]]> ≤0.5 ≤0.5
[0153] Note: The surface resistance of the inner layer before kneading in Table 4 is shown in Table 1;
[0154] The following conclusions can be drawn from the above test results:
[0155] The antistatic aluminum-plastic films prepared in Examples 5-7 are referred to as aluminum-plastic film a, aluminum-plastic film b, and aluminum-plastic film c, respectively; the aluminum-plastic films prepared in Comparative Examples 1-2 are referred to as aluminum-plastic film d and aluminum-plastic film e, respectively.
[0156] In Examples 5-7, the surface resistance of the antistatic aluminum-plastic film and the inner polyethylene heat-sealing film is 10. 6 ~10 9 Within the Ω range, the electrostatic dissipation requirements of antistatic materials are met; as the amount of carbon black-graphene polyethylene composite masterbatch increases, the surface resistance of the inner layer gradually decreases and the electrostatic decay time is significantly shortened, indicating that carbon black-graphene hybrid particles can form a stable and continuous point-to-surface synergistic conductive network in the polyethylene matrix.
[0157] Comparative Example 1 uses polyethylene masterbatch with low carbon black content. Due to the poor dispersibility of carbon black particles and insufficient filler content, it is difficult to form a continuous conductive path, and the surface resistivity is at 10. 12 The surface resistivity is on the order of Ω, exhibiting poor electrostatic decay performance; in Comparative Example 2, increasing the content of ordinary carbon black can reduce the surface resistivity to 10. 7 The amount of carbon black is on the order of Ω, but its heat-sealing strength is significantly reduced, indicating that simply increasing the amount of carbon black will destroy the continuity of the polyethylene heat-sealing layer and the molecular chain diffusion ability.
[0158] The heat-sealing strength test results show that the heat-sealing strength of the antistatic aluminum-plastic film in Examples 5-7 is greater than 50 N / 15 mm, which is significantly higher than that of the comparative example. This indicates that the present invention achieves chemical bonding between carbon black and graphene through a dialdehyde alkenyl functionalized modifier, and further improves the dispersion and interfacial bonding of conductive filler in polyethylene through grafting reaction between alkenyl functional groups and polyethylene matrix. This achieves good heat-sealing performance while obtaining antistatic properties.
[0159] The barrier performance test results show that the oxygen permeability and water vapor permeability of each embodiment are lower than the detection limit of the test method, and no pinholes are detected. This indicates that the antistatic modification mainly acts on the inner polyethylene composite film and will not damage the barrier integrity of the middle aluminum foil layer. After rubbing, the surface resistance of the inner layer of the antistatic aluminum-plastic film in Examples 5-7 still remains within the antistatic range, and the oxygen permeability and water vapor permeability are still lower than the detection limit. This indicates that its antistatic stability and barrier stability are good during packaging, transportation and use.
Claims
1. An antistatic aluminum-plastic film, characterized in that, It is made by dry lamination of an outer nylon film, a middle aluminum foil layer and an inner polyethylene composite film; The polyethylene composite film is composed of 60-80wt% metallocene linear low-density polyethylene resin and 20-40wt% carbon black-graphene polyethylene composite masterbatch. Carbon black-graphene polyethylene composite masterbatch comprises the following raw materials in parts by weight: 9-9.6 parts linear low-density polyethylene resin; 0.3-0.6 parts carbon black-graphene hybrid particles; 0.03-0.06 parts initiator; The carbon black-graphene hybrid particles were prepared by a Schiff base reaction between a dialdehyde alkenyl functionalized modifier and amino-functionalized carbon black and amino-functionalized reduced graphene oxide. The mass ratio of amino-functionalized carbon black, amino-functionalized reduced graphene oxide and dialdehyde alkenyl functionalized modifier was 1:0.2-0.4:1-3. The chemical structural formula of the dialdehyde alkenyl functionalized modifier is: 。 2. The antistatic aluminum-plastic film according to claim 1, characterized in that, The preparation method of the dialdehyde alkenyl functionalized modifier is as follows: Diethanolamine undergoes an amine addition reaction with allyl methacrylate via a secondary amine and an α-β-unsaturated alkenyl group, with the molar ratio of diethanolamine to allyl methacrylate controlled at 1:1; a dihydroxyalkenyl-functionalized intermediate is obtained. The dihydroxyenyl functionalized intermediate undergoes an esterification reaction of hydroxyl groups and acyl chloride with chloroacetyl chloride, with the molar ratio of the dihydroxyenyl functionalized intermediate to chloroacetyl chloride controlled at 1:2; thus, the dichloroenyl functionalized intermediate is obtained. The dichloroalkenyl functionalized intermediate undergoes a substitution reaction between the chlorine functional group and the hydroxyl group of p-hydroxybenzaldehyde. By controlling the molar ratio of the dichloroalkenyl functionalized intermediate to p-hydroxybenzaldehyde to be 1:2, a dialdehyde-alkenyl functionalized modifier is prepared.
3. The antistatic aluminum-plastic film according to claim 1, characterized in that, The amino-functionalized carbon black is prepared by silanizing carbon black with hydroxyl-rich surface by 3-aminopropyltriethoxysilane; the mass ratio of 3-aminopropyltriethoxysilane to carbon black is 0.04-0.1:
1.
4. The antistatic aluminum-plastic film according to claim 1, characterized in that, The amino-functionalized reduced graphene oxide is prepared by silanizing graphene oxide with 3-aminopropyltriethoxysilane and then reducing it with diethanolamine as a reducing agent; the mass ratio of 3-aminopropyltriethoxysilane, diethanolamine and graphene oxide is 5-10:4-6:
1.
5. The antistatic aluminum-plastic film according to claim 3, characterized in that, The average particle size of the carbon black is 5-15 nm.
6. The antistatic aluminum-plastic film according to claim 4, characterized in that, The average sheet diameter of the graphene oxide is 2-8 μm.
7. The antistatic aluminum-plastic film according to claim 1, characterized in that, The initiator is dicumyl peroxide or benzoyl peroxide.
8. A method for preparing an antistatic aluminum-plastic film as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Initiator, carbon black-graphene hybrid particles and linear low-density polyethylene resin are added to a twin-screw extruder according to the formula. After melt grafting reaction, the mixture is extruded and granulated to obtain carbon black-graphene polyethylene composite masterbatch. The twin-screw extruder has the following temperature zones: Zone 1: 150-170℃; Zone 2: 170-190℃; Zone 3: 190-210℃; Zone 4: 200-225℃; Zone 5: 200-220℃; Zone 6: 190-215℃; Screw speed: 60-120 r / min; Melt grafting reaction time: 5-20 min. Step 2: Using metallocene linear low-density polyethylene resin and carbon black-graphene polyethylene composite masterbatch as raw materials, the raw materials are put into the hopper of a single screw extrusion blown film machine according to the formula dosage, stirred and mixed evenly, the molten resin is gathered at the die head through the distributor, extruded and blown through the die head, cooled, and wound up to obtain a polyethylene composite film. The temperatures of each zone of the single-screw extrusion blown film machine are as follows: Zone 1 125-135℃, Zone 2 150-160℃, Zone 3 170-180℃, flow channel temperature 165-175℃, screw speed 30-50 r / min, and blow-up ratio 2.3-2.
6. Step 3: Apply two-component polyurethane adhesive between the outer nylon film and the middle aluminum foil layer, and between the middle aluminum foil layer and the inner polyethylene composite film, respectively. After drying, laminating, and curing, an antistatic aluminum-plastic film is obtained; wherein the dry adhesive coating amount is 2.0-5.0 g / m². 2 The drying temperature is 60-90℃, the composite pressure is 0.2-0.8MPa, the curing temperature is 40-60℃, and the curing time is 24-72h. The side of the polyethylene composite film that is laminated with the aluminum foil is corona treated, and the surface tension after corona treatment is 38-44mN / m. The other side of the polyethylene composite film serves as the inner heat-sealing layer of the antistatic aluminum-plastic film.
9. The method for preparing an antistatic aluminum-plastic film according to claim 8, characterized in that, The outer nylon film has a thickness of 15-25 μm, the middle aluminum foil layer has a thickness of 7-20 μm, and the inner polyethylene composite film has a thickness of 95-110 μm.
10. An application of the antistatic aluminum-plastic film as described in any one of claims 1-7, characterized in that, The antistatic aluminum-plastic film is used for packaging lithium iron phosphate powder, the positive electrode material for lithium batteries.